The effectiveness of CEFR-aligned Arabic language instruction in Islamic economics education: Motivational and achievement outcomes - Uus Rustiman; Eka Kurnia Firmansyah (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2026)
This study examines the effectiveness of CEFR-aligned Arabic language instruction in Islamic economics education, focusing on its impact on student motivation and academic achievement. While Arabic is essential for understanding Islamic economic terminology derived from the Qur'an and Hadith, traditional Arabic instruction in Indonesian Islamic economics programs often remains disconnected from disciplinary content. Using a descriptive-analytical method with a sample of 80 students from Universitas Padjadjaran, this study employed pre-test and post-test assessments, motivation questionnaires, and classroom observations. The findings reveal that CEFR-aligned instruction significantly improves both motivation (from 65% to 86% engagement) and learning outcomes (mean score increase from 62 to 81). Students demonstrated enhanced communicative competence in Arabic terminology relevant to Islamic finance, halal certification, and supply chain governance. The study recommends the systematic adoption of CEFR standards in Arabic for Specific Purposes (ASP) curricula and the development of specialized instructional materials for Islamic economics contexts. Ultimately, this research provides an evidence-based pedagogical blueprint for higher education institutions to effectively bridge the gap between theoretical linguistic instruction and the pragmatic demands of the global halal industry.